Paradigma Baru Keadilan Restoratif dalam Sosiologi Hukum Islam Indonesia: Respons Nahdlatul Ulama dan Muhammadiyah terhadap Penanganan Korupsi - Suparno, Suparno; Rusli, Rusli; Hidarya, Ia (Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study explores the application of restorative justice as a new paradigm in the sociology of Islamic law in Indonesia, focusing on corruption cases and the responses of the two largest Islamic organizations: Nahdlatul Ulama (NU) and Muhammadiyah. The study addresses the limitations of the retributive paradigm, which has long dominated the justice system but has proven insufficient in achieving substantive justice and social restoration. The aim is to examine the compatibility of restorative justice with Islamic legal principles and to analyze NU and Muhammadiyah’s perspectives and recommendations on its implementation in combating corruption. This research employs a qualitative method with normative-sociological approaches through literature analysis and in-depth interviews. Findings reveal that restorative justice aligns closely with Islamic values such as sulh (reconciliation), islah (social reform), maslahah (public interest), and ‘afw (forgiveness). NU emphasizes moral and fiqh-based aspects, requiring full restitution and moral accountability, while Muhammadiyah advocates structural legal reforms, anti-corruption education, and integrity monitoring. The implication is that integrating restorative justice into the Indonesian Islamic legal framework could enhance social justice, legal efficiency, and public acceptance—provided that implementation is supported by strict regulations and transparent oversight mechanisms.